The Importance of Being Treacherous: Betrayals in Amitav Ghosh’s "Flood of Fire" - Piciucco, Pier Paolo (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2020)
The possible link in the parallel stories that overlap in the elaborate plot of Flood of Fire (2015) by Amitav Ghosh may be identified in the repeated actions of betrayal, occurring as a part of a sentimental, military, or ideological conspiracy and involving all the protagonists of the narratives. Far from evaluating them as immoral, however, the narrator seems to go to great lengths to demonstrate that, although this recurrent switching-of-sides at the moment causes stress and pain to many characters, these actions invariably prove to be the only fitting solutions to major problems in the long term. This expedient is used by Ghosh in order to validate the prominent theory in Cultural Studies that identities are constantly modified and treacherous attitudes are inevitable.